Effects of Local Ischemic Compression on Upper Limb Latent Myofascial Trigger Points: A Study of Subjective Pain and Linear Motor Performance. (4th March 2019) - Esparza, Danilo; Aladro-Gonzalvo, Arian R.; Rybarczyk, Yves
Abstract : Objective . To analyse the effect of the manual ischemic compression (IC) on the upper limb motor performance (MP) in patients with LTrPs. Materials and Methods . A quasiexperimental study was performed in twenty subjects allocated to either patients group with LTrPs (PG, n=10) or healthy group with no symptoms (HG, n=10). Subjective pain and linear MP (movement time and Fitts' Law) were assessed before and after a linear tapping task. Data were analysed with mixed factorial ANOVA for intergroup linear motor performance differences and dependent t-student test for intragroup pain differences. Results . PG had a linear MP lower than the HG before treatment ( p < 0.05). After IC, the PG showed a significant decrease of pain (4.07 ± 1.91 p < 0.001). Furthermore, the movement time (15.70 ± 2.05 p < 0.001) and the Fitts' Law coefficient (0.80 ± 0.53 p < 0.001) were significantly reduced. However, one IC session did not allow the PG to get the same MP than the HG ( p < 0.05). Conclusion . The results suggest the IC effectiveness on pain and MP impairment in subjects with LTrPs. However, the MP of these patients is only partially improved after the IC application.